Antibacterial activity and chemical analysis of fruit oil of Trachyspermum ammi Linn. Sprague - Premakumara, G.A.S.; Kathirgamanathar, S.; Thayalini, T.; Bandara, V.S.; Thevanesam, V.; Arawwawala, L.D.A.M. (Journal of Ayurvedic and Herbal Medicine 2016; 2(4): 117-119, 2016)
In traditional medicine, the fruit of Trachyspermum ammi (Family: Umbelliferae), commonly known as Asamodagam in Sinhala; Omum in Tamil and Ajowan or Bishop’s weed in English is used in gastro intestinal disorders (loss of appetite, dyspepsia, diarrhea, abdominal pains, abdominal distension and vomiting) and respiratory diseases (Bronchial asthma). The water distillate (omatheeneer or oma water or asamodagam spirit) is used for stomach problems in children. The fruits of this plant are used in different forms such as powder, decoction and oma water in adults also. It is reported that essential oil and the solvent extracts of fruits are active against Salmonella typhi, Escherichia coli, Lactobacillus sp. and Bacillus licheniformis. Objective and Methodology: An attempt was taken to investigate the (a) antimicrobial properties of essential oil of T. ammi fruits against 8 human pathogens: Staphylococcus aureus (NCTC 6571), Escherichia coli (NCTC 10418), Pseudomonas aeruginosa (NCTC 10662) and five wild strains of Methicillin resistant Staphylococcus aureus (MRSA) by disc diffusion method and (b) chemical composition of the essential oil of T. ammi fruits by Gas Chromatography (GC). Results: Essential oil of T. ammi showed inhibitory activity against all tested microorganisms. The zone of inhibition was ranged from 21–30 mm The major compound present in the essential oil of T. ammi fruits was thymol (60.7%) followed by -cymene (21.7%) and -terpinene (13.6%). Conclusion: Findings of the present study will be helpful to develop antiseptic creams or lotions from fruits of T. ammi essential oil.
Keywords: Antibacterial activity; Gas chromatography; Trachyspermum ammi